Survey research in practical theology and congregation studies - Hermans, C.; Schoeman, W. J. (Faculty of Theology, University of the Free State, 2015)
Empirical research is understood as the search for knowledge-based empirical data. The best-known data-based research strategy is survey research. In practical theology, survey research is probably one of the most used research strategies. In the exploration of congregational life, a broader (quantitative) lens is required in order to investigate congregations. The aim is to explore the use of survey research in practical theology and congregational studies. First, we shall describe survey research as a methodology, in order to explain its relevance as an empirical method for doing practical theology. Secondly, we shall explain the relevance of survey research for congregational life. Surveys make a valuable contribution to congregational studies, as they provide a quantitative perspective on congregational life and its context. National and local demographics are an important part of the positioning and ecology of a congregation. Thirdly, we shall evaluate the relevance and contribution of the survey research methodology for congregational studies
Keywords: Survey research; Practical theology